Perpaduan Problem Based Learning dengan Pendekatan Open Ended untuk Meningkatkan Hasil Belajar Siswa - Amelia, Linda; Susilaningtyas, Tri (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2021)
The purpose of this study is to improve student learning outcomes in studying Algebraic Forms using a Combination of Problem-Based Learning with an Open-Ended Approach. This type of research includes Classroom Action Research (PTK), with the procedure in this study using a cycle model. From the research results, the percentage of student learning outcomes in cycle I reached 77% than in cycle II reached 100%. Meanwhile, student learning activities increased from cycle I to cycle II, namely 72% to 89%. This proves that the level of student understanding increases with the application of the Combined Problem Based Learning with the Open Ended Approach, so that learning can properly provide an illustration with examples of its basic illustrations.